Developing funware best eagle for digital literacy in elementary schools - Muhamad Afandi; Mia Oktavia (Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was prompted by the observed deficiency in students’ comprehension of the rights and obligations of school community members—a gap that has significant implications for their daily conduct and interpersonal behavior. Employing a quasi-experimental design, the research involved two groups—experimental and control—each comprising 30 fourth-grade elementary school students. Data were collected through a combination of knowledge assessments, attitude observation checklists, and self-reflection questionnaires. The resulting data were analyzed using independent sample t-tests and descriptive statistical methods. The findings reveal that the implementation of project-based learning (PjBL) strategies—specifically poster creation and collaborative group discussions—led to a statistically significant enhancement in students’ understanding of civic responsibilities, as evidenced by an average increase of 15% in post-intervention scores (p < 0.05). Furthermore, notable improvements were observed in students’ attitudes, particularly in dimensions of responsibility and collaboration, as indicated by both observational and self-reflective measures. These results suggest that project-based authentic assessment constitutes an effective pedagogical approach for fostering both cognitive and affective development in elementary civic education.